2016
DOI: 10.1097/sla.0000000000001426
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-analysis of Current Experience in Treating IPNB

Abstract: Early surgery is advisable for radiologically suspected IPNB as it is frequently invasive. The pathobiology of IPNB demonstrates geographic variation. Pancreaticobiliary IPNB expresses MUC1 and is more frequently associated with invasive disease than other IPNB subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
68
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 44 publications
3
68
1
Order By: Relevance
“…IPNB accounts for 7%-38% of all bile duct carcinomas, and 40%-80% of IPNBs contain invasive carcinomas [3,6]. However, IPNB is generally less invasive and has a more favorable outcome than conventional bile duct cholangiocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…IPNB accounts for 7%-38% of all bile duct carcinomas, and 40%-80% of IPNBs contain invasive carcinomas [3,6]. However, IPNB is generally less invasive and has a more favorable outcome than conventional bile duct cholangiocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The intrahepatic bile ducts showed no changes such as dilatation on preoperative images. Previous reports have indicated that most IPNB patients present with right hypochondria (35-88.5%), recurrent acute cholangitis (5-59%), and obstructive jaundice (20-36%) [4-6]), but that IPNB may also be detected incidentally in asymptomatic individuals (5-12%) [3,4]. IPNB remains difficult to differentiate from cholangiocarcinoma and other types of bile duct disease, and may mimic colon cancer metastases on radiological findings [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, three types of pre-invasive lesion of bile duct tumor were also indicated in the sixth edition of the General Rules for Clinical and Pathological Studies on Cancer of the Biliary Tract in 2013 as follows: i) biliary intraepithelial neoplasm, ii) IPNB or intracystic papillary neoplasm, and iii) mucinous cystic neoplasm (17). IPNB-originating advanced bile duct carcinoma has also been reported (18,19). However, the definitive similarity and differentiation between IPNB and associated biliary neoplasms may still be unclear in some cases.…”
mentioning
confidence: 99%